Description of the Nutritional Status of Pregnant Women With Anemia in Rumbio Village, Panyabungan Utara District, Mandailing Natal Regency, 2022 - Nurkholidah; Siti khadijah (PT Inovasi Pratama Internasional, 2022)
Nutritional status is Anemia is a condition in which the number and size of red blood cells are below the normal limit value. Anemia is still a health problem in Indonesia. Anemia is a public health problem that affects low, middle and high income countries and has an adverse impact on health, social and economic development. this research aims to determine nutritional status in Rumbio Village. This research is a cross-sectional descriptive in nature, using primary data obtained from questionnaires and then distributed to pregnant women. The sample used in this study was a total sampling technique, which was obtained from the entire population, namely 20 respondents. From the results of the research conducted, it showed that the respondents' knowledge about the nutritional status of pregnant women regarding the incidence of anemia was based on the age of the majority 20-35 years of 10 respondents (50%), based on the majority of middle education as many as 17 respondents (85%), based on the occupation of the majority of farmers as 9 respondents (45%), based on BMI the majority had normal nutritional status as many as 17 respondents (85%) and based on LILA the majority also had normal status as many as 16 respondents (80%), based on HB the majority were normal as many as 17 respondents (85%) had less knowledge in the age group of 20-35 years there were 13 respondents (65%). Based on the results of the study on the Overview of Nutritional Status of Pregnant Women Against Anemia Incidence, the majority of anemia occurs in pregnant women with poor nutritional status, both based on BMI and LILA, each of 1 person (100%).